Haematological and haemodynamic changes in hypovolemic dogs - Ercan Keskin; Mursayettin Eksen (Eurasian Journal of Veterinary Sciences)
In this study, same haematological and haemodynamic changes in hypovolemic dogs were investigated. For this purpose totally 20 dogs were usedas a material. The dogs were anesthetized with thiopenthal sodium (30 mg/kg iv), and the n haemorrhagic shock was performed experimentally. The mean arterial pressure (MAP) was reduced to 40±5 mmHg and maintained at this level for 30 min (Hypotensive period). The blood samples for the determinatfon of hemogram and blood gases analyses were taken before the experiment and at the e nd of the hypotensive period and other paramaters were recorded. Be fare the experiment the me an alterfal press u re (MAP), the mean systo/ic arterfal pressure (MSAP) and the mean diastolic arterfal pressure (MDAP) were found to be 120. 7, 151.4 and 105.4 mmHg, respectively. These values were found to be 41.5, 54. 0 and 35.3 mmHg at the end of the hypotensive period, respectevely. On the other hand, before the experiment while the mean heart rate and the mean respiration rate were found to be 64.3 and 15. 6, the same values were determined to be 102.2 and 33 at the and of the hypotensive period, respective!y. At the and of the hypotensive period, the mean values of WBC, haematocrft and haemog!obin levels decreased drastical!y when they were compared with the levels before the experiment. At the en d of the hypotensive period, ap H and vpH, aHCO3 and vHCO3, apCO2 atCO2 and vtCO2, vo2 saturation, aO2 and vO2 concentration !eve/s decreased. On the other h and, at the e nd of the hypotensive period the mean arterial base excess (aBE) and venous base excess (vBE) levels decreased drastically.